Analisis Pertimbangan Hakim Menjatuhkan ‘Uqubat Terhadap Anak sebagai Pelaku Jarimah Pemerkosaan dalam Putusan Nomor 1/JN ANAK/2022/MS.Skm - Trisiyah, Nur Okta; Asy’ari; Efendi, Sumardi; Hidayat, Roni (FAKULTAS SYARIAH DAN EKONOMI ISLAM UNIVERSITAS ISKANDARMUDA BANDA ACEH, 2023)
This research aims to uncover the sanctions imposed in cases of rape committed by minors in accordance with Law No. 11 of 2012 on the juvenile criminal justice system and Aceh Qanun No. 6 of 2014 on Islamic criminal law. Furthermore, the study also seeks to explore the considerations taken by judges in determining sanctions for cases of rape involving minors, as specified in Decision No. 1/JN Anak/2022/MS.Skm, which addresses cases of rape by minors. The research methodology employed is a qualitative descriptive approach, involving data collection through interviews, observations, and documentation. The findings of this study reveal that in the juvenile criminal justice system, the sanctions for rape cases involve serving half of the adult criminal sentence. In contrast, under the Qanun Jinayat, sanctions for rape by minors under the age of consent encompass one-third of the adult sentence, which may include corporal punishment, fines, or imprisonment. Furthermore, judges take into consideration the demands of the public prosecutor, defense arguments presented by legal counsel, community reports, and recommendations from guardians or parents of the minor, all while not disregarding the psychological well-being of the victim.